Innovations in Pharmaceutical Manufacturing through Edge AI for Process Optimization and Standard Compliance - Anil Kumar,; Nitu Sehrawat,; Kaushal Sharma,; Vijay Kumar,; Megha Sehgal, (The Bioscan, 2025)
EdgeAI integrates artificial intelligence with edge computing, enabling real-time decision-making in industrial applications. In pharmaceutical manufacturing, EdgeAI enhances process efficiency, predictive maintenance, and quality control by analyzing data locally, reducing cloud dependency, and improving system responsiveness. This paper examines the role of EdgeAI and embedded systems in optimizing pharmaceutical production, ensuring regulatory compliance, and minimizing downtime. A review of recent advancements highlights how AI-driven edge computing enables rapid fault detection, automated drug formulation monitoring,